PENGARUH PEMBERIAN REBUSAN DAUN SIRSAK TERHADAP PENCEGAHAN KANKER PAYUDARA STADIUM AWAL DIDESA KOTO GADANGJAYA ( KOJA) KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Nora Ervina Sembiring; Adi - Arianto; Sri Sudewi Pratiwi Sitio; Daniel Suranta Ginting (Jurnal Penelitian Keperawatan Medik, 2020)
Breast cancer is a disease that is caused by excessive growth or uncontrolled development of breast cells (tissue). According to the American Cancer Society 2016, cancer is the leading cause of death in Asia, America, Hawaii and the Pacific Islands with a proportion of 27% of all deaths with cancer most common in men prostate cancer 18% lung cancer 14% colorectal cancer 12% whereas for women, the most common cancer is 34% (WHO 2017). Soursop is a plant that can grow and bear fruit throughout the year in soil conditions with sufficient water content. Soursop fruit is composed of 67% edible fruit flesh, 20% skin 8.5% seeds and 4% the central axis of the fruit from the overall weight of the fruit. To analyze the effect of soursop leaf decoction on the prevention of early-stage breast cancer. research design uses one group pretest posttest design. The variables in this study were soursop leaf stew as an independent variable and prevention of early-stage breast cancer as the dependent variable. The population in this study were all women who had early stage breast cancer. Sampling using a purposive sampling technique of 10 respondents. Intervention will be carried out by giving soursop leaf stew 2 times one day. Data were collected using questionnaire and paired sample T test. The results of the study showed that there were physical changes in breast cancer patients. Shaphiro-wilk data normality test results before giving soursop leaf decoction is 8.8 and after given soursop leaf decoction is 4.1. Paired sample test results show that the data p: 0,000 <α: 0.05 then Ho is rejected and Ha is accepted. Which means that there is an influence of soursop leaf decoction there is prevention of early-stage breast cancer.